2012
DOI: 10.4236/jssm.2012.51008
|View full text |Cite
|
Sign up to set email alerts
|

Animal Handling during Supply for Marketing and Operations at an Abattoir in Developing Country: The Case of Gudar Market and Ambo Abattoir, Ethiopia

Abstract: In the agricultural sector, it is important to appropriately develop livestock resources in of developing countries in order to reduce poverty. The aim of this study was to investigate the animal handling and welfare issues during transport for marketing with special focus on cattle flow to and from Gudar livestock market and activity chain of Ambo abattoir in Ethiopia. Information and data on main feeder markets to Gudar regional market; the main stakeholders in this animal supply chain; number of animals flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…In Ethiopia, the most common transport system was on foot from rural areas to nearby markets and then by vehicles to urban areas such as Kera and shola market around Addis Ababa [18]. Since almost all animals were transported by walking on rocky and asphalted roads full of gravel to urban areas, they were exposed to the incidence of lameness and injury to the bone and muscle, swelling of the leg, and inflammation [19]. Traffic accidents are also major problems when they were transported by vehicles [19].…”
Section: Transport Of Farm Animalsmentioning
confidence: 99%
“…In Ethiopia, the most common transport system was on foot from rural areas to nearby markets and then by vehicles to urban areas such as Kera and shola market around Addis Ababa [18]. Since almost all animals were transported by walking on rocky and asphalted roads full of gravel to urban areas, they were exposed to the incidence of lameness and injury to the bone and muscle, swelling of the leg, and inflammation [19]. Traffic accidents are also major problems when they were transported by vehicles [19].…”
Section: Transport Of Farm Animalsmentioning
confidence: 99%
“…A recent study indicated that stakeholders in Ethiopia handle animals in an aversive way, which has been shown to increase prevalence of death and injuries [32]. By measuring behavioural or physiological conditions, animal handling can be explained to a higher extent and a welfare concept implemented.…”
Section: Farm Animal Welfare and Handling In Ethiopiamentioning
confidence: 99%
“…The most common way of transporting animals in Africa is by foot since there is a great lack of vehicles with sufficient capacity [4]. Walking animals by foot often leads to injured, dead or stolen animals, which were investigated by Bulitta, et al, [32] who found that 7.6% of animals died, 6-9% got injured and 2.8% were stolen. Furthermore, he found that lameness and injuries such as swelling of legs commonly occur.…”
Section: Farm Animal Welfare and Handling In Ethiopiamentioning
confidence: 99%
See 2 more Smart Citations